2015 Beers Criteria and STOPP v2 for detecting potencially inappropriate medication in community-dwelling older people: prevalence, profile and risk factors. - Blanco-Reina, Encarnación; Valdellós, Jenifer; Aguilar-Cano, Lorena; García-Merino, Maria Rosa; Ocaña-Riola, Ricardo; Ariza-Zafra, Gabriel; Bellido-Estevez, Inmaculada (Springer, 2019)
Purpose To comparatively assess the prevalence rates of potentially inappropriate medications (PIMs) obtained by the former and latest versions of American Geriatrics Society Beers Criteria (AGS BC) and screening tool of older person’s potentially inappropriate prescriptions (STOPP), and analyze the factors of influence on PIM. Methods Cross-sectional study including 582 community-dwelling older adults over the age of 65. Sociodemographic, clinical, functional, and comprehensive drug therapy data were collected. The primary endpoint was the percentage of patients receiving at least one PIM. Results A total of 3626 prescriptions were analyzed. PIMs were detected in 35.4% and 47.9% of patients according to the STOPP v1 and the 2012 AGS BC, respectively. This percentage rose to 54% when 2015 AGS BC were used and reached 66.8% with STOPP v2. The kappa coefficient between STOPP v2 and its former version was lower than the one between the updated Beers Criteria and their former version (0.41 vs 0.85). The agreement was good (0.65) between both latest criteria. The number of medications, psychological disorders, and insomnia were predictors of PIM. A novel finding was that bone and joint disorders increased the odds for PIM by 78%. Conclusions The 2015 AGS BC showed high sensitivity and good applicability to the European older patients. Both updated tools identified some pharmacological groups (benzodiazepines, PPIs, and opioids, among others) and certain health problems (insomnia, psychological disorders, and osteoarticular diseases) as factors of influence on PIM. Based on these findings, interventions aimed at promoting appropriate use of medications should be developed.
https://openpolicyfinder.jisc.ac.uk/id/publication/7963
Keywords: Ancianos - Consumo de medicamentos; Residencias de ancianos; Farmacología clínica; Atención farmacéutica; Potentially inappropriate medications; 2015 Beers Criteria; STOPP v2 Criteria; Community-dwelling older adults; Cross-sectional study